Work and Digital Technologies. A Proposal for Analysis - Gosetti, Giogio (Italian Sociological Review, 2024)
This article aims to review the digitalization of work by adopting a multidimensional analytical perspective on the quality of working life that examines the different aspects of working conditions. It is divided into three sections: (1) contextualization of digitalization as part of certain changes already underway, (2) determination of the specific nature of digitalization, (3) presentation of the features of the analytical framework to study quality of working life and feasible ways to study the impact of digitalization. It is not within the scope of this paper to provide an overview of literature on the effects of digitalization. Instead, it offers a conceptual-methodological basis for the interpretation of digitalization, focusing on field analysis.